Cardiovascular Complications in Coronavirus Disease 2019—Pathogenesis and Management - Restrepo, Marcos I.; Marin-Corral, Judith; Rodriguez, Juan J.; Restrepo, Valeria; Cavallazzi, Rodrigo (Seminars in Respiratory and Critical Care Medicine, 2023)
The coronavirus disease 2019 (COVID-19) pandemic has caused a devastating impact on morbidity and mortality around the world. Severe acute respiratory syndrome-coronavirus-2 has a characteristic tropism for the cardiovascular system by entering the host cells and binding to angiotensin-converting enzyme 2 receptors, which are expressed in different cells, particularly endothelial cells. This endothelial injury is linked by a direct intracellular viral invasion leading to inflammation, microthrombosis, and angiogenesis. COVID-19 has been associated with acute myocarditis, cardiac arrhythmias, new onset or worsening heart failure, ischemic heart disease, stroke, and thromboembolic disease. This review summarizes key relevant literature regarding the epidemiology, diagnosis, treatment, and preventive measures related to cardiovascular complications in the setting of COVID-19.
Keywords: COVID-19; cardiovascular events; complications